Abdominal Pain after Gastric Bypass: Labor, Uterine Rupture, or Obstruction and Internal Hernia - Sarah N. Cross; Unzila Nayeri; Andrew Duffy; Christian M. Pettker (Case Reports in Obstetrics and Gynecology)
Background. Although gastric bypass may reduce obesity-related complications of subsequent pregnancies, surgical complications requiring antenatal and postpartum interventions are not uncommon. Case. A 26-year-old G4P1112 status post-Roux-en-Y gastric bypass required multiple urgent antenatal evaluations due to frequent episodes of abdominal pain. At 35 + 4 weeks, she presented with severe abdominal pain; initial evaluation was negative for gastrointestinal pathology. The patient was found to be in preterm labor and underwent a repeat cesarean section. The postoperative course was complicated by bowel obstruction due to internal hernia resulting in an emergent laparotomy and a prolonged hospital course. Conclusion. As more reproductive-aged women opt for surgical treatment of obesity, it is essential that obstetricians recognize complications to be able to counsel and appropriately care for these patients.